The impact of foreign trade activities on the economy of Uzbekistan: factors of macroeconomic growth and innovative development (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Foreign trade activity is an important driving force in the development of the national economy. This process allows diversifying state budget revenues by accelerating macroeconomic growth rates, creating new jobs and activating the labor market. Also, through foreign trade, advanced technologies and innovative solutions are introduced into the national economy, which serves to increase production efficiency and improve product quality. In the case of Uzbekistan, through pragmatic trade and economic strategies, the country is effectively integrating into the international economic ecosystem.